Do firms learn by exporting or learn to export? Evidence from Senegalese manufacturing plant - Cissé Fatou; Ji Eun Choi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The increasing quantity of literature investigating the impact of trade openness on firm efficiency has not yet provided a definite prediction of the direction of causality. This paper investigates how the relationship between exporting and productivity impacts on manufacturing sectors in Senegal. Using unique firm-level panel data for the period 1998 - 2011, we estimate productivity and exporting dynamics, controlling for other unobserved effects, and using General Method of Moments. Our results indicate evidence both that the most efficient firms self-select for entry into the export market and that learning has an impact on the export market. From a policy perspective, this evidence of learning by exporting suggests Senegal has much to gain from encouraging exports by helping domestic firms overcome barriers to entering foreign markets, particularly by investing in skilled workers and promoting access to patents and licenses.
Keywords: C33; D24; F14; L25; 330; exporting; total factor productivity; learning by exporting; general method of moments